Periodized training programme and technical performance of age-group gymnasts - Lacordia, R. C.; Godoy, E. S.; Vale, R. G. S.; Sposito-Araujo, C. A.; Dantas, E. H. M. (International Journal of Sports Science and Coaching, 2011)
The present study evaluates the influence of a periodized training programme on the technical performance of beginner gymnasts. The sample population, consisting of 17 artistic gymnasts, all female, between 8 and 13 years of age, was divided into two groups: an experimental group (EG; n = 9) and a control group (CG; n = 8). Initially, both groups underwent a diagnostic evaluation to determine the baseline technical level of the athletes. Both groups then underwent a 24-week training programme involving three hour-long sessions per week. The EG participated in a periodized programme, while the CG had no periodization. At the end of the training period, both groups underwent another diagnostic evaluation (post-test), which revealed a higher technical level among those who had taken part in the periodized training programme.